Naipauls A Bend in the River as a Jamesonian Third World National Allegory - Idris, Nazua (Stamford Journal of English, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/sje.v7i0.14472 Stamford Journal of English; Volume 7; Page 169-182